Perendaman Ekstrak Daun Sirih Terhadap Nilai Kelulushidupan dan Profil Darah Ikan Nila (Oreochromis niloticus) - Bintang, Yustika Eka Fauziah (Fakultas Perikanan dan Ilmu Kelautan, 2024)
The use of betel leaf extract as a natural medicinal ingredient. Treatment can be done using the soaking method. The aim of this research is to determine the effect of immersion in betel leaf extract on the survival and blood profile of tilapia fish. This research used an experimental method with 4 treatments (control, 400 ppm, 600 ppm, 800 ppm). The research parameters are the survival and blood profile of tilapia which includes hemoglobin, hematocrit, blood glucose, leukocyte differentiation and water quality. After maintenance for 5 days, the research results showed that the survival rate of tilapia fish ranged from 40-80%. Blood profile values include hemoglobin, hematocrit and blood glucose values respectively in the range of 7-8.1 g/dL, 20.85 - 23.85% and 47 - 104.5 mg/dL. The percentage values of leukocyte differentiation which include monocyte, lymphocyte and polymorphonuclear values are 16.5 – 23.5%, 54 – 61.4% and 18- 23.5%, respectively. The temperature in the maintenance pond is 26-27oC, pH is 6-8 and Dissolved Oxygen (DO) is 3.4-3.9. The water quality of the tilapia rearing pond is still within the normal range.